Anatomy of the extraneural blood supply to the intracranial oculomotor nerve. Issue 2 (February 1996) - Cahill, M; Bannigan, J; Eustace, P
Abstract : AIMS: An anatomical study was undertaken to determine the extraneural blood supply to the intracranial oculomotor nerve. METHODS: Human tissue blocks containing brainstem, cranial nerves II-VI, body of sphenoid, and associated cavernous sinuses were obtained, injected with contrast material, and dissected using a stereoscopic microscope. RESULTS: Eleven oculomotor nerves were dissected, the intracranial part being divided into proximal, middle, and distal (intracavernous) parts. The proximal part of the intracranial oculomotor nerve received extraneural nutrient arterioles from thalamoperforating arteries in all specimens and in six nerves this blood supply was supplemented by branches from other brainstem vessels. Four nerves were seen to be penetrated by branches of brainstem vessels and these penetrating arteries also supplied nutrient arterioles. The middle part of the intracranial oculomotor nerve did not receive nutrient arterioles from adjacent arteries. The distal part of the intracranial oculomotor nerve received nutrient arterioles from the inferior cavernous sinus artery in all 11 nerves and in seven nerves this was supplemented by a tentorial artery arising from the meningohypophyseal trunk. The inferior hypophyseal artery arose from the meningohypophyseal trunk in all 11 cavernous sinuses dissected. CONCLUSION: This study shows a constant pattern to the blood supply of the intracranial oculomotor nerve. It also highlights the close relation between the blood supplies to the intracavernous oculomotor nerve and the pituitary gland.